(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تميز القرن العشرين بأحداث كبرى توالت بسرعة مذهلة، ولكن أهم ما تميز به ثورة تكنولوجيا المعلومات،وانطلاقاً من هذه الأهمية ، رأينا دراسة تأثير المعلوماتية على العملية التعليمية في المنطقة الساحلية وذلك من خلال مقارنة بين التعليم في مجتمع المعلومات والتعليم التقليدي ،ودراسة الواقع الراهن لانتشار المعلوماتية في التعليم ما قبل الجامعي والتعليم الجامعي والتعليم عن بعد.وبناءً على هذه الدراسة تم التوصل إلى عدد من النتائج أهمها: -وجود فروقات واضحة بين طريقتي التعليم التقليدي والتعليم القائم على تكنولوجيا المعلومات والاتصالات. -ازدياد عدد مراكز التدريب والتأهيل المفتتحة لتدريس المعلوماتية. -ازدياد أعداد الطلاب المستفيدين من مادة المعلوماتية في مرحلة التعليم ما قبل الجامعي. -رفد القطاعات الصناعية والخدمية والإنتاجية بخريجي كليات المعلوماتية وحسب الاختصاصات المناسبة. -دخول التعليم عن بعد إلى سوريا من خلال الجامعة الافتراضية. The twentieth century was distinguished by great events succeeded in an amazingly fast way, but the important thing distinguishing it was the emergence of informatics technology. Based on this importance, we preferred studying the effects of the informatics on the learning process in the costal region through a comparison between learning in informatics society and classical learning, besides studying the recent status of the spread of informatics in pre-academic, academic and correspondence learning. According to this study, we have reached many results, the most important of which are: 1- The existence of obvious differences between traditional method of teaching and the teaching method depending on informatics. 2- The increase in the number of informatics training centers. 3- The increase in the number of students who get benefit from informatics in the pre-academic stage. 4- Providing the industrial, service and production fields with graduates from the faculty of informatics according to the proper specialties. 5- Distant teaching has entered Syria through the Virtual University.